2021
DOI: 10.1190/geo2019-0215.1
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal amplitude variation with offset parameterization and inversion for fracture weaknesses in tilted transversely isotropic media

Abstract: The characterization of fracture-induced tilted transverse isotropy (TTI) seems to be more suitable to actual situation of geophysical exploration for fractured reservoirs. Fracture weaknesses enable us to describe the fracture-induced anisotropy. With the incident and reflected PP-wave in TTI media, we propose a robust method of azimuthal amplitude variation with offset (AVO) parameterization and inversion for fracture weaknesses in a fracture-induced reservoir with TTI symmetry. Combining the linear-slip mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Later, other studies developed approaches to further describe the anisotropy in specific media with certain anisotropy patterns or fracture orientations and provided ways to implement such anisotropy in existing algorithms (e.g. Faria and Stoffa, 1994;Zhou and Greenhalgh, 2005;Martins, 2006;Chen et al, 2017;Meléndez et al, 2019;Pan et al, 2021). In particular, Zhou et al (2008) demonstrated the effect of anisotropy on crosshole travel-time tomography results for tilted transversely isotropic media.…”
Section: Introductionmentioning
confidence: 99%
“…Later, other studies developed approaches to further describe the anisotropy in specific media with certain anisotropy patterns or fracture orientations and provided ways to implement such anisotropy in existing algorithms (e.g. Faria and Stoffa, 1994;Zhou and Greenhalgh, 2005;Martins, 2006;Chen et al, 2017;Meléndez et al, 2019;Pan et al, 2021). In particular, Zhou et al (2008) demonstrated the effect of anisotropy on crosshole travel-time tomography results for tilted transversely isotropic media.…”
Section: Introductionmentioning
confidence: 99%
“…Later, other studies developed approaches to further describe the anisotropy in specific media with certain anisotropy pattern or fracture orientations and provided ways to implement such an anisotropy in existing algorithms (e.g. Faria and Stoffa, 1994;Zhou and Greenhalgh, 2005;Martins, 2006;Chen et al, 2017;Meléndez et al, 2019;Pan et al, 2021). In particular, Zhou et al (2008) demonstrated the effect of anisotropy on crosshole traveltime tomography results for tilted transversely isotropic media.…”
Section: Introductionmentioning
confidence: 99%